New liquid carbon dioxide based strategy for high energy/power density LiFePO4 - Hwang, Jieun; Kong, Ki Chun; Chang, Wonyoung; Jo, Eunmi; Nam, Kyungwan; Kim, Jaehoon (ELSEVIER, 2017)
A liquid carbon dioxide (l-CO2) based coating approach is developed for ultrathin, uniform, and conformal carbon coating of hierarchically mesoporous LiFePO4 (LFP) nano/microspheres for fabricating high-energy-density and high-power-density carbon coated LFP (C-LFP) with long-term cyclability. The unique properties of l-CO2 result in an ultrathin carbon layer (1.9 nm) distributed all over the primary nano-sized LFP particles (20-140 nm in diameter), forming a core (LFP)-shell (carbon) structure. This unique structure provides facile penetration of liquid electrolytes and rapid electron and Li-ion transport. C-LFP exhibits high reversible capacity, high energy and power density (168 mAh g(-1) at 0.1 C, 109 Wh kg(-1) and 3.3 kW kg(-1) at 30 C, respectively) with excellent long-term cyclability (84% cycle retention at 10 C after 1000 cycles). In addition, the ultrathin and uniform carbon layer of the mesoporous microspheres allows a high tap density (1.4 g cm(-3)) resulting in a high volumetric energy density (458 Wh L-1 at a 30 C rate). Furthermore, C-LFP presents a high capacity and stable cycling performance under low-temperature and high-temperature environment. Well-developed carbon coating approach in this study is simple, scalable, and environmentally benign, making it very promising for commercial-scale production of electrode materials for large-scale Li-ion battery applications.
Keywords: CATHODE MATERIAL; ELECTROCHEMICAL PERFORMANCE; OLIVINE LIFEPO4; CONDUCTIVE NETWORK; NANOPOROUS CARBON; RATE CAPABILITY; QUANTUM-DOTS; LITHIUM; MICROSPHERES; STORAGE